Assessment of fluency dynamics in climbing - Seifert, L.; Hacques, G.; Rivet, R.; Legreneur, P. (Sports Biomechanics, 2024)
The aim of this study was to investigate the hold-by-hold climbing fluency dynamics by using an instrumented holds system that measured the contact time on each hold. Forty-four competitive climbers have been analysed in a regional lead climbing competition during a route composed of 41 instrumented holds on 11 m high artificial climbing wall and with a grade of difficulty 6b on the French scale (IRCRA reported scale: 13). After removing 10 climbers who fell before the top of the route, the 34 remaining climbers who completed the route were clustered according to their total contact time on each hold. The hierarchical cluster analysis distinguished four profiles of climbing fluency dynamics, on the basis of six "crux" points, showing that the fastest climbers at the crux points were those with the shortest climbing time. This new instrumented-holds system appeared very innovative as it provides an instantaneous feedback to coaches regarding inter-limbs fluency and subsequent motor organisations.